On the taxonomic status of Cicada orni Linnaeus (Hemiptera, Cicadidae) from Lesbos island in Greece - Simões, Paula Cristina; Boulard, Michel; Quartau, José Alberto (Zootaxa, 2006)
A male of Cicada orni Linnaeus, 1758 from the island of Lesbos (Greece) was found in a recent study to be different from the typical species on the basis of longer echemes and a higher peak frequency. As such it was described as the new subspecies C. orni lesbosiensis Boulard, 2000. The present study is a more thorough analysis of the calling song of further material of C. orni collected in the island of Lesbos as well as in the surrounding area, i.e., other Aegean islands and the Greek and Turkish mainlands. This acoustic signal was recorded, comparatively analysed in time and frequency domains and no significant differences were found between this Lesbos sample with nearby populations. Therefore, the present results do not support the designation of the Lesbos material as an independent subspecies.